Depletion of Arctic ozone in the winter 1990 - Koike, M.; Kondo, Y.; Hayashi, M.; Iwasaka, Y.; Newman, P. A. (1991)
Ozone mixing ratios were measured by ozonesondes on board balloons launched from Esrange, near Kiruna, Sweden (68 deg N, 20 deg E) from January 11 to February 9, 1990. The data obtained prior to a sudden warming on February 7, 1990 show that at potential temperatures between 460 and 640 K, the ozone mixing ratio just inside the polar vortex was systematically smaller than that outside, the largest difference being 29 percent at around 525 K. The ozone mixing ratio at 525 K inside the vortex decreased at a rate of about 1.5 percent per day between January 26 and February 4. The temperatures simultaneously observed were quite often low enough to allow for formation of nitric acid trihydrate particles around this altitude. Depletion of ozone due to highly perturbed chemical conditions in late January and early February is strongly suggested.